Quitting experiences and preferences for a future quit attempt: a study among inpatient smokers. Issue 4 (17th April 2015) - Thomas, Dennis; Abramson, Michael J; Bonevski, Billie; Taylor, Simone; Poole, Susan G; Weeks, Gregory R; Dooley, Michael J; George, Johnson
Abstract : Objective: Understanding smokers' quit experiences and their preferences for a future quit attempt may aid in the development of effective cessation treatments. The aims of this study were to measure tobacco use behaviour; previous quit attempts and outcomes; methods used to assist quitting; difficulties experienced during previous attempts; the motives and preferred methods to assist quitting in a future attempt; identify the factors associated with preferences for smoking cessation. Design: Face-to-face interview using a structured questionnaire. Setting: Inpatient wards of three Australian public hospitals. Participants: Hospitalised smokers enrolled in a smoking cessation trial. Results: Of 600 enrolled patients (42.8% participation rate), 64.3% (n=386) had attempted quitting in the previous 12 months. On a scale of 1 (low) to 10 (high), current motivation to quit smoking was high (median 9; IQR 6.5–10), but confidence was modest (median 5; IQR 3–8). Among 386 participants who reported past quit attempts, 69.9% (n=270) had used at least one cessation aid to assist quitting. Nicotine replacement therapy (NRT) was most commonly stated (222, 57.5%), although the majority had used NRT for <4 weeks. Hypnotherapy was the most common (68, 17.6%) non-pharmacological treatment. Over 80% (n=311) experienced withdrawal symptoms; craving and irritability were commonly reported. Most participants (351, 58.5%) believed medications, especially NRT (322, 53.7%), would assist them to quit in the future. History of previous smoking cessation medication use was the only independent predictor of interest in using medications for a future quit attempt. Conclusions: The majority of smokers had attempted quitting in the previous 12 months; NRT was a popular cessation treatment, although it was not used as recommended by most. This suggests a need for assistance in the selection and optimal use of cessation aids for hospitalised smokers. Trial registration number: Australian and New Zealand Clinical Trials Registry: ACTRN12612000368831.